The Construct of Economic Law Thought of Abul A'la Maududi in the Contemporary Era - Rahmat Husein Lubis; Afri Hasni Putra (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2025)
This study aims to find out how the construction of Islamic economic law thought from Abul A'la Maududi to the current development of contemporary Islamic economics. Abul A'la Maududi is a prominent Islamic economist. Abul A'la Maududi is better known in the socio-politics between Islam in the world. This type of research is a type of qualitative research with a method of collecting data through literature studies. Where the researcher will collect several book or journal materials related to the construction of Abul A'la Maududi's thought. And the researcher will analyze descriptively the construction of Abul A'la Maududi's Islamic economic legal thought. The result of this research is that Abul A'la Maududi's thinking on economic law seeks to offer a holistic system and in accordance with Islamic teachings. The principles he put forward underlined the importance of balancing individual and social interests, the fair distribution of wealth, and the role of the state in ensuring economic justice. In the contemporary era, the construction of Abul A'la Maududi's thought still has relevance, especially in efforts to overcome economic inequality and fight for economic justice based on Islamic values.